An Evaluation of the Covid-19 National Economic Recovery Program: Evidence From MSMEs’ Performance in West Java, Indonesia - Apriliana, Agnes Ridla; Masudi, Ahmad Aswin (Indonesian Journal of Business and Entrepreneurship, 2025)
Background: Micro, Small, and Medium Enterprises (MSMEs) maintain their performance through internal factors, like their characteristics as MSMEs, and external factors, such as government policy. The National Economic Recovery Program (PEN) was expected to improve the performance of MSMEs, especially during the pandemic. Purpose: This study aims to evaluate the impact of PEN (credit restructuring, digitalization, and training) and MSMEs' characteristics (form of business, gender, level of education, type of MSMEs, marketing area) on MSMEs' performance measured by total asset turnover. Design/methodology/approach: The data from a survey conducted by Cooperation and MSMEs Dinas Koperasi dan UMKM, West Java Province, between 2020 and 2021. This survey focuses on 8,469 comprehensive and compliant MSME data points out of 9,046 using the logistic model.Finding/Result: The results show MSMEs who participate in PEN have a higher log odds ratio of total asset turnover above the average than those who do not. The form of business, gender, and marketing area positively affect the log odds ratio of total asset turnover above the average. Vocational education leads to the highest asset turnover, followed by diplomas, universities, and high schools. Service and Industry SMEs outperform other sectors, followed by Convection and Fashion, Food and Beverage, and Craft and Accessories. Conclusion: MSMEs involved in the PEN program are more likely to achieve higher asset turnover, with business form, gender, education, and marketing area significantly influencing performance.Originality/value (State of the art): This study uniquely links MSME characteristics with the government recovery program, providing a fresh evaluation of how policy interventions and internal drive MSME performance during the pandemic. Keywords: MSMEs, PEN, The National Economic Recovery Program, West Java, COVID-19